2021
DOI: 10.21440/2307-2091-2021-1-142-149
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors affecting the market capitalization of the largest oil companies in Russia

Abstract: Relevance. The stock exchange prices of shares reflect the view from the market position of the value of a particular public company: the market capitalization of the issuing company acts as a value indicator. The volatility of stock prices, on the other hand, determines the dynamics of market capitalization. In this regard, the problem of market capitalization management and its forecasting in the future becomes urgent. Taking into account the raw materials orientation of the Russian economy, enterprises of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Theoretical and practical issues related to discount rate determination for commodity companies were previously raised by the authors of the article. In particular, in study [1] it was found that from the point of view of theory, the discount rate is, firstly, the minimum rate of profit that the investor is counting on, and secondly, alternative profitability, that is, an alternative to the project or business being evaluated as a whole . From the standpoint of practice, the САРМ (Capital Asset Pricing Model) proposed by U.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical and practical issues related to discount rate determination for commodity companies were previously raised by the authors of the article. In particular, in study [1] it was found that from the point of view of theory, the discount rate is, firstly, the minimum rate of profit that the investor is counting on, and secondly, alternative profitability, that is, an alternative to the project or business being evaluated as a whole . From the standpoint of practice, the САРМ (Capital Asset Pricing Model) proposed by U.…”
Section: Methodsmentioning
confidence: 99%
“…From the standpoint of practice, the САРМ (Capital Asset Pricing Model) proposed by U. Sharp was named as the most correct formula for calculating the indicator under review: (1) where Rf is the risk-free rate of return, %; β -"beta" coefficient, acting as a measure of market risk, reflecting the sensitivity of changes in the value of assets depending on market profitability;…”
Section: Methodsmentioning
confidence: 99%